COMPARATIVE ANALYSIS AND CULTURAL SIGNIFICANCE OF PHRASEOLOGICAL UNITS IN UZBEK AND ENGLISH LANGUAGES - Karshieva Gulsara Ahmadaliyevna (Journal Park Publishing, 2025)
This article presents a comprehensive comparative analysis of phraseological units in the Uzbek and English languages, focusing on their linguistic structure, semantic features, and deep-rooted cultural significance. Phraseological units, or idiomatic expressions, are essential elements of any language that reflect the worldview, mentality, and values of the people who speak it. The study investigates both universal and culturally specific phraseological phenomena, emphasizing how national identity, historical development, religion, traditions, and social norms shape idioms and fixed expressions in each language. Through a cross-linguistic comparison, the article categorizes phraseological units into thematic groups such as those related to human behavior, nature, animals, family, emotions, and moral values. It highlights similarities that demonstrate shared human experiences as well as differences that reveal the uniqueness of each culture’s cognitive and communicative approaches. In addition, the research explores how metaphor and symbolism function in idioms, shedding light on the role of cultural metaphors and conceptual imagery in the formation of phraseological units. The article also analyzes the pragmatic and stylistic roles these units play in daily speech, literature, media, and folklore, offering insights into how idioms contribute to the expressive richness and communicative efficiency of language. Special attention is given to translation challenges and strategies when dealing with non-equivalent or culture-bound expressions. The findings of this study are valuable for linguists, translators, language learners, and educators, as they provide a deeper understanding of the intersection between language, culture, and cognition in English and Uzbek.
Keywords: Phraseological unit, idiom, cultural significance, metaphor, Uzbek, English, worldview, comparative analysis, translation equivalence.